Retinal oxygen metabolism in exudative age-related macular degeneration. - Geirsdottir, Asbjorg; Hardarson, Sveinn Hakon; Olafsdottir, Olof Birna; Stefánsson, Einar (Acta Ophthalmologica, 2014)
To access publisher's full text version of this article click on the hyperlink at the bottom of the page To determine whether retinal vessel oxygen saturation in patients with exudative age-related macular degeneration (AMD) is different from that of a healthy population. Oxygen saturation was measured in retinal arterioles and venules in 46 eyes of 46 treatment-naïve exudative AMD patients and 120 eyes of 120 healthy controls. Simple and multiple linear regression analyses were used to compare the two study groups. Oxygen saturation in retinal venules increases with age in patients with exudative AMD (0.45 ± 0.19% per year; p = 0.026), while it decreases with age in healthy individuals (-0.13 ± 0.03% per year; p = 0.0002). The slopes are statistically different (ANCOVA; p = 0.0003). The reverse is true for the arteriovenous difference in oxygen saturation, which decreases with age in AMD patients (-0.29 ± 0.16% per year; p = 0.065) and increases in healthy individuals (0.12 ± 0.03% per year; p < 0.0001). At age 80 years, AMD patients have 2.7 percentage points higher venous oxygen saturation than healthy persons and 4.2 percentage points less arteriovenous difference. The data suggest that retinal oxygen metabolism may be altered in exudative AMD. The arteriovenous difference is smaller in exudative AMD than in a healthy cohort, consistent with reduced oxygen extraction by retinal vessels in AMD patients. Further studies are needed to fully understand the role of retinal oxygen metabolism in the pathophysiology of exudative AMD. Prevention of Blindness Fund Landspitali-University Hospital Research Fund Rasmussen Foundation University of Iceland Research Fund Icelandic Centre for Research (Rannis)